Prevalence of anticonvulsant-induced vitamin D deficiency - E. A. Dontseva; P. I. Pilipenko; N. A. Shnayder; M. M. Petrova; R. F. Nasyrova (Эпилепсия и пароксизмальные состояния, 2022)
Background. Epilepsy is a common disease in children and adults, requiring long-term or lifelong use of antiepileptic drugs (AEDs) in 60% of cases. Enzyme-inducing and enzyme-inhibiting AEDs may have a negative effect on vitamin D metabolism. However, at present, standard treatment protocols for patients with epilepsy include no nutrients and vitamin-mineral vitamin D containing complexes.Objective: to analyze studies on the prevalence of vitamin D deficiency induced by AEDs intake in patients with epilepsy.Material and methods. The search for full-text publications in Russian and English was carried out in еLibrary, PubMed/ MEDLINE, ClinicalKey, Google Scholar databases, covering the last five years. The analysis included 9 domestic and 54 foreign epidemiological studies assessing prevalence of AED-induced vitamin D deficiency and, consequently, altered bone mineralization and osteomalacia/osteoporosis.Results. Both in children and adults, the prevalence of AED-induced vitamin D deficiency reaches 40% and even higher. The region of residence of patients with epilepsy does not significantly affect this indicator. Impaired bone mineralization is associated with AED-induced vitamin D deficiency and requires the inclusion of vitamin D in the protocols of disease-modifying epilepsy therapy in children and adults.Conclusion. The results of the review showed high relevance of the discussed interdisciplinary problem and need to introduce laboratory screening of vitamin D deficiency among pediatric and adult patients with epilepsy.